Compact and General Strategy for Solving Current and Potential Distribution in Electrochemical Cells Composed of Massive Monopolar and Bipolar Electrodes. Issue 11 (1st January 2017) - Colli, A. N.; Girault, H. H.
Abstract : A compact, fast and general algorithm based on Dirichlet boundary conditions for the potential field is derived to enable the calculation of local current distribution, shunt currents and the local potential distribution on massive electrodes in electrochemical cells of any type of geometry in three dimensions, composed of bipolar electrodes at an unknown floating potential and/or terminal monopolar electrodes. The algorithm allows performing the calculation of current-potential distributions and bypass currents for a fixed cell potential (potentiostatic) or a fixed cell current (galvanostatic) enforced to the cell. The proposed approach can be extended to take into account concentration variations of one or several species inside the cell or electrical conductivity variations due to the presence of separators or liquid-gas-solid phases. In order to validate the algorithm, a detailed comparison, between the suggested strategy with experimental results is made in the case of secondary current distribution for i ) a segmented one bipolar electrode ii ) a cell stack composed of 14 bipolar electrodes in the industrial process of alkaline water electrolysis. The proposed tool can help designers to develop more efficient electrochemical reactors by comparing results using different electrode materials, electrolytes and cell designs.